Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                
0% found this document useful (0 votes)
36 views

1.3 - Function Operations & Composition of Functions

Uploaded by

Rishabh Nagda
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
0% found this document useful (0 votes)
36 views

1.3 - Function Operations & Composition of Functions

Uploaded by

Rishabh Nagda
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
You are on page 1/ 22

Unit 1

Notes 1.3

Function
Operations
A relation is a set of ordered pairs or a rule
that produces one or more output numbers
for every valid input number.
(every x has at least one y)

A function is a relation that gives a single


output number for every valid input number.
(every x has only one y)
In order for a relationship to be a function…
EVERY INPUT MUST HAVE AN OUTPUT

TWO DIFFERENT INPUTS CAN HAVE THE


SAME OUTPUT (y can “cheat” / repeat)

ONE INPUT CAN HAVE ONLY ONE


OUTPUT (x can’t “cheat” / repeat)
Test if a graph is a function:
The Vertical Line Test

If it is possible for a vertical line to


intersect a graph at more than one
point, then the graph is NOT the graph
of a function.
Use the vertical line test to visually check if the
relation is a function.

(4,4)
(-3,3)

(1,1)

(1,-2)

Do not have to copy! Function?


No, Fails the
Vertical line Test.
Function? YES!

Do not have to copy!


Function? NO!

Do not have to copy!


Function? NO!

Do not have to copy!


Function? YES!

Do not have to copy!


Write the equation of the line and determine if it
is a function.

D: (−∞, ∞) D: [−𝟓]
R: [𝟒] R: (−∞, ∞)

This is a
vertical line
This is a
horizontal line

Slope: 0 Slope: undefined


Equation: 𝒚 = 𝟒 Equation: 𝒙 = −𝟓
Function? Function?
Yes – it passes the VLT. No – it fails the VLT.
One x for every y. X repeats.
f(x) + g(x)
(f+g)(x) = ____________________

f(x) – g(x)
(f-g)(x) = ____________________

f(x)  g(x)
(fg)(x) = ____________________
æfö f(x )
ç ÷ (x) = g(x )
ègø
Ex. 1
f(x) = x − 3 x − 5 and g(x) = x + 2
2
Given
x − 4x − 7
2
Find (f - g)(x) = ____________________
(x 2
)
− 3x − 5 − (x + 2)
(x 2
− 3x − 5) + (− x − 2)
Sub 2 for x !

− 11
Find (f - g)(2) = ______
Ex. 2
Given f(x) = x + 1 and g(x) = x − 1
x 2
− 1
Find (f•g)(x) = _____________

(x + 1)(x − 1)
x −1
2

Sub -3 for x !

8
Find (f•g)(-3) = _______
Ex. 3
Let 𝒇 𝒙 = 𝟐𝒙𝟐 + 𝟖 and 𝒈 𝒙 =𝒙−𝟑
Find 𝒇 + 𝒈 and 𝒇−𝒈

(f + g)(x) = 2x2 + x + 5

(f – g)(x) = 2x2 – x + 11
Ex. 4 Given 𝒇 𝒙 = 𝟐𝒙 − 𝟓
and 𝒈 𝒙 = 𝟑𝒙 + 𝟖
𝒇
Find (𝟓)
𝒈
𝒇 𝒇(𝟓)
𝟓 =
𝒈 𝒈(𝟓)
𝒇 𝒙 = 𝟐𝒙 − 𝟓
𝒇 𝟓 = 𝟐(𝟓) − 𝟓 𝒇 𝟓
𝒇 𝟓 =𝟓 𝟓 =
𝒈 𝟐𝟑
𝒈 𝒙 = 𝟑𝒙 + 𝟖
𝒈 𝟓 = 𝟑(𝟓) + 𝟖
𝒈 𝟓 = 𝟐𝟑
Ex. 5 Given f(x) = 6x and g(x) = 2x
𝒇
𝒇 3 ( )(x) = 3
Find ( )(x) = _____________ g
g
𝒇 𝟔𝒙 y=3
( )(x) = Horizontal
g 𝟐𝒙 Line

𝒇 All y’s = 3
Find ( )(4) 3
= ______ no matter
𝒈 what x

Sub 4 for x. Hmmm…..


When x=4,y=3
Unit 1

Notes 1.3

Composition of
Functions
Composition of Functions involves substituting one
function into another function anywhere you see that
variable.
Two ways to write composition of functions:

(𝒇 ∘ 𝒈)(𝒙) 𝒇(𝒈 𝒙 )
The 2nd function becomes
the inside function

This is read as “f of g of x”.


This does NOT mean “f of g times x”.
You are not multiplying the two functions.
You will take the function for g(x) [the inside function] and
substitute it into f(x) [the outside function] anywhere you
see an “x” [the variable].
Ex. 1 𝒇 𝒙 = 𝟑𝒙 + 𝟏𝟎 𝒈 𝒙 = 𝟓𝒙 − 𝟒

Find (𝒇 ∘ 𝒈)(𝒙) 𝒇(𝒈 𝒙 ) = 𝒇(𝟓𝒙 − 𝟒)


= 𝟑(𝟓𝒙 − 𝟒) + 𝟏𝟎
= 𝟏𝟓𝒙 − 𝟏𝟐 + 𝟏𝟎
𝒇(𝒈 𝒙 ) = 𝟏𝟓𝒙 − 𝟐

Find 𝒇(𝒈 −𝟒 ) = −𝟔𝟐


Method 1 Method 2
Substitute −4 into Evaluate 𝑔(−4) Sub. −24 in for 𝑔(−4)
𝑓 𝑔 𝑥 = 15𝑥 − 2 𝑓 𝑔 −4
𝑔 −4 = 5 −4 − 4
𝑓 𝑔 −4 = 15(−4) − 2 𝑓 −24
𝑔 −4 = −24
𝑓 𝑔 −4 = −60 − 2 𝑓 −24 = 3 −24 + 10
𝑓 𝑔 −4 = −62 𝑓 −24 = −62
Ex. 2 𝒇 𝒙 = 𝟑𝒙 + 𝟏𝟎 𝒈 𝒙 = 𝟓𝒙 − 𝟒

Find (𝒈 ∘ 𝒇)(𝒙) 𝒈(𝒇 𝒙 ) = 𝒈(𝟑𝒙 + 𝟏𝟎)


= 𝟓 𝟑𝒙 + 𝟏𝟎 − 𝟒
= 𝟏𝟓𝒙 + 𝟓𝟎 − 𝟒
𝒈(𝒇 𝒙 ) = 𝟏𝟓𝒙 + 𝟒𝟔
Find 𝒈(𝒇 𝟑 ) = 𝟗𝟏
Method 1 Method 2
Substitute 3 into Sub. 19 in for 𝑓(3)
Evaluate 𝑓(3)
𝑔 𝑓 𝑥 = 15𝑥 + 46 𝑔 𝑓 3
𝑓 3 = 3 3 + 10
𝑔 𝑓(3 ) = 15 3 + 46 𝑔 19
𝑓 3 = 19
𝑔 𝑓 3 = 45 + 46 𝑔 19 = 5 19 − 4
𝑔 𝑓 3 = 91 𝑔 19 = 91
Ex. 3
Given f(x) = x − 3 x − 5 and g(x) = x + 2
2

x 2
+ x − 7
Find f(g(x)) = _______________
𝑓 𝑥 + 2 = (x + 2) − 3(x + 2) − 5
2

𝑥+2 𝑥+2 −3 𝑥+2 −5


x + 4 x + 4 − 3x − 6 − 5
2

Sub 2 for x !
−1
Find (f◦g)(2) = _____
= (𝟐)𝟐 + 𝟐 − 𝟕
=𝟒+𝟐−𝟕
2x 1
Ex. 4 Given f(x) = 3
and g(x) = 2
x

4x
Find f(f(x)) = _________
9

𝟐𝒙 𝟐𝒙 𝟒𝒙
𝟐 𝟑 𝟒𝒙 𝟑 𝟒𝒙 𝟏
𝒇 = 𝟑 = = ÷ = ⦁
𝟑 𝟑 𝟑 𝟏 𝟑 𝟑
𝟑

Sub 3 for x ! 4
Find (f◦f)(3) = ________
3
4(3) 12
= =
9 9

You might also like